Strategic change management in public sector organisations / David Baker - Baker, David
This book covers all the major aspects of change management for those working in public sector and not-for-profit organisations. It summarises key theories and approaches to change management and includes detailed, worked descriptions of key techniques used in change management processes. and programs, with extensive reference to case studies drawn from a range of public sector, not-for-profit organizations and other environments. Written by a highly knowledgeable and well-respected practitioner in the fieldDraws on the author's wide-ranging practical experience of major organizational development and change management in a wide range of situation Applies as well as describes theoryProvides practical and realistic solutions to real-world problems